2011
DOI: 10.2214/ajr.10.6401
|View full text |Cite
|
Sign up to set email alerts
|

Female Breast, Lung, and Pelvic Organ Radiation From Dose-Reduced 64-MDCT Thoracic Examination Protocols: A Phantom Study

Abstract: The results of this anthropomorphic phantom study showed substantial and significant variation in radiation doses to the breast and lungs depending on the scanning protocol used with the potential for over threefold dose reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Our study supports the use of tube voltage and heart rate reduction to decrease ARD and is in synchrony with Matsubara et al who obtained similar results on phantom studies with 64-row CT angiography [18]. Litmanovich et al [20] also found better ARD profile in 64-row MDCT phantom study by using imaging protocols with lower tube voltage which was in consensus with an earlier study by Hurwitz et al [21, 22]. Our study adds to the literature by documenting similar trend of kVp and HR variation on ARD seen in radiosensitive organs when using 320-row mode.…”
Section: Discussionsupporting
confidence: 91%
“…Our study supports the use of tube voltage and heart rate reduction to decrease ARD and is in synchrony with Matsubara et al who obtained similar results on phantom studies with 64-row CT angiography [18]. Litmanovich et al [20] also found better ARD profile in 64-row MDCT phantom study by using imaging protocols with lower tube voltage which was in consensus with an earlier study by Hurwitz et al [21, 22]. Our study adds to the literature by documenting similar trend of kVp and HR variation on ARD seen in radiosensitive organs when using 320-row mode.…”
Section: Discussionsupporting
confidence: 91%
“…For CT examinations of the thorax, the breast is always in the scanning range but is not an organ of interest. Any possible effort to reduce radiation dose to the breast should be made considering the radiosensitive glandular tissue of the female breast [4][5][6][7][8]. Bismuth breast shielding is an effective method for reducing the radiation dose in the breast from 29% to 63% [6,[9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…These values achieved are at the very low end of the dose ranges published 5,18,20,21 despite being obtained in routine clinical settings and in an unselected population with a wide range of BMI, spanning from 15.8 to 48.8. Additionaly, the lower radiation dose achieved with iterative image reconstruction was associated with a significantly better objective and subjective image quality than standard filtered back projection, suggesting possible further dose reduction.…”
Section: Resultsmentioning
confidence: 90%
“…Given the vast variety of protocols, techniques, and (if implemented) dose reduction strategies published in the literature, the dose ranges for routine pulmonary MDCTA vary substantially. Organ doses to the breast ranged from 3.9 to 20 mGy 15,20,21 . However, in the study of Hurwitz et al 18 , on 120 kV and 140 kV protocols, large anthropomorphic phantom measurements showed average breast doses of 44 mGy at 120 kV and even 62 mGy when scanning at 140 kV (without breast shielding).…”
Section: Discussionmentioning
confidence: 99%